Two-dimensional transitional metal dichalcongenide heterostructures : interface optical properties - Zheng, ShouJun (2018)
Since the first report of graphene in 2004, atomically thin materials become more and more attractive to researchers due to their unique properties and promising applications. For example, two-dimensional (2D) transitional metal dichalcogenides (TMDCs), such as MoS2, WSe2, exhibit band gap transitions from indirect one in bulk to direct one in monolayer. Additionally, monolayer MoS2 is flexible and tough material with a high Young’s modulus, comparable to the stainless steel. There are many applications based on atomically thin TMDCs, including field effect transistors (FETs), photodetectors and so on. Furthermore, band gap engineering of 2D TMDCs by fabricating the heterojunctions including lateral and van der Waals junctions paves the way to study the novel electronic transport, interlayer coupling and charge transfer. In this thesis, I will focus on the fabrication and characterization of 2D TMDCs and their heterostructures. First, I will present the fabrication of lateral alloyed heterojunctions of WxMo1-xS2/MoS2 by chemical vapor deposition method. The heterojunctions have been characterized by photoluminescence (PL) and Raman spectra to support our conclusion. In the monolayer heterojunction, the photoluminescence peak shifts continuously from 686.8 nm at triangle center to 633.4 nm at the edge at excitation wavelength of 457 nm. The part of WxMo1-xS2 is attested to be composition-graded alloy according to the position dependent PL peaks and we also calculated the composition of this alloy. This heterojunction with a tunable band gap may have potential applications in wide range photodetectors and multi-color light emitters. Then, I will present the interlayer coupling of WS2 bilayers and trilayers, grown by the CVD method. Both the interlayer distance and twisted angle affect the interlayer coupling in 2D TMDCs, and further change the band structures. I will show that random-twisted WS2 bilayers (except of 0 and 60 degrees) behave as quasi-direct band gap materials due to the weakened interlayer coupling. Theoretical calculation based on the density functional theory shows the enlarged interlayer distance in the twisted bilayer WS2. A new peak was observed in the PL spectra in the twisted WS2 bilayer or trilayer, which is contributed to the interlayer exciton which is composed of one electron in the top (bottom) layer and one hole in the bottom (top) layer. Next, I will show the evident cathodoluminescence (CL) emission from monolayer TMDCs, including WSe2, MoS2 and WS2, in the van der Waals configuration by sandwiched them in two hexagonal boron nitride (hBN) layers. In the hBN/TMDC/hBN heterostructure, e-beam induced e-h pairs can transfer to and be trapped in the middle TMDC layer, leading to increased recombination probability within the TMDC layer. The emission intensity is almost linearly proportional to the thickness of the top or bottom hNB layers. Moreover, I will demonstrate that CL can be applied to study the strain-induced excitonic peak shift in the suspended monolayer TMDCs. Finally, as a related project, I will present the multiple phase transitions of 1T-TaS2 induced by an external electrical filed at room temperature. The number of electrically driven phase transitions is proved to depend on the thicknesses of flakes. The threshold of the electric field in the phase transition is also revealed. Additionally, gate tunable phase transitions were realized by combining the TaS2 and graphene together.